Physicochemical and FTIR Study of Diesel-Hydrogen Peroxide Fuel Blend - Khan, M.S. (Institute of Physics Publishing, 2018)
Physicochemical properties of combustion fuels play a key role in determining the qualitative and quantitative characteristics, reliability and health effects associated with emissions. This paper reports the preparation of polysaccharide (PS) based emulsifier for stable blending of petroleum diesel-hydrogen peroxide (H2O2) and investigated the influence of H2O2 as diesel fuel blends on the physicochemical properties and characteristics. The quantity of PS-emulsifier was kept at 5 volume (vol. ) and the volume ratio of H2O2 were varied 5-15 vol. to reference diesel (RD), respectively. The blended diesel/H2O2 fuel were prepared under inert oxygen (O2) gas closed heating system; afterthought, physiochemical properties of diesel/H2O2 blend were evaluated at standard ASTM D-975 testing method. The kinetic properties show the interaction of RD and H2O2 blend at presence of PS emulsifier which exhibit the phenomenon to diminish the interfacial tension among the two different phases to form a homogenized stable solution. Results revealed that H2O2 is capable of enhancing the diesel fuel properties and showed that the addition of H2O2 in a diesel fuel blend are lied within the ranges of standard ASTM D-975. Due to further oxygen atom present in H2O2, it can facilitate the combustion process which ultimately effect on exhaust emission. Â© Published under licence by IOP Publishing Ltd.